Postpartum Coronary Vasospasm with Literature Review - Jayanth Koneru; Matthew Cholankeril; Kunal Patel; Fadi Alattar; Ashraf Alqaqa; Hirtaj Virk; Fayez Shamoon; Mahesh Bikkina (Case Reports in Cardiology)
Acute myocardial infarction during pregnancy or the postpartum period is rare. We report a case of a 39-year-old postpartum woman who developed non-ST-elevation myocardial infarction due to severe diffuse coronary vasospasm. To our knowledge, this is the first case of angiographically evidenced coronary vasospasm, in a postpartum woman, with resistance to intracoronary nitroglycerin.